Some Concepts Of Green Supply Chain Management Using Particle Swarm Optimization Algorithm (Trinity Journal of Management, IT & Media (TJMITM), 2020)
Green Supply Chain management for green warehouse with environmental concerns a technique based on Particle Swarm Optimization algorithm to optimize inventory in the whole green supply chain. We focus on to specifically determine the dynamic nature of the excess stock level and shortage level required for inventory optimization in the green supply chain such that the total Green Supply Chain management for green warehouse with environmental concerns cost is minimized. The complexity of the problem increases when more products and multiple agents are involved in Green Supply Chain management for green warehouse with environmental concerns process that has been resolved in this work. Here, we are proposing an optimization methodology that utilizes the Particle Swarm Optimization algorithm, one of the best optimization algorithms, to overcome the impasse in maintaining the optimal stock levels at each member of the Green Supply Chain management for green warehouse with environmental concerns. We apply our method on four member of Green Supply Chain management for warehouse studied model for optimization.
Keywords: Green warehouse; Green Supply Chain; Two-Green Agents; Environmental collaboration; Particle Swarm Optimization algorithm